2019
DOI: 10.46357/bcnaturais.v14i2.177
|View full text |Cite
|
Sign up to set email alerts
|

Microbial inoculants produced from solid waste compost for bioremediation of diesel-contaminated soils

Abstract: A atividade microbiana pode ser estimulada a promover a remoção de hidrocarbonetos no solo ao se introduzir microrganismos hidrocarbonoclásticos. Inoculantes microbianos foram produzidos utilizando-se composto de lixo sólido municipal (CLSM) para a biorremediação de solos contaminados com óleo diesel. A aplicação de diesel ocorreu a cada quatro dias para o inoculante A e a cada oito para o inoculante B. Análises respirométricas, contagem de bactérias heterotróficas totais e avaliação de hidrocarbonetos totais … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, there could be initial competition with indigenous microbes 69 , 71 . A means of eliminating such competition was demonstrated by Leal et al 76 in the treatment of mature compost with diesel and allowed to stand for 21 days purposely to ensure an abundance of PHDM before mixing with diesel contaminated soil. Also, Nwankwegu and Onwosi 69 suggested that immobilized PHDM on biocarriers has improved remediation performance and eliminates competition with indigenous microbes.…”
Section: Soil Remediation Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…However, there could be initial competition with indigenous microbes 69 , 71 . A means of eliminating such competition was demonstrated by Leal et al 76 in the treatment of mature compost with diesel and allowed to stand for 21 days purposely to ensure an abundance of PHDM before mixing with diesel contaminated soil. Also, Nwankwegu and Onwosi 69 suggested that immobilized PHDM on biocarriers has improved remediation performance and eliminates competition with indigenous microbes.…”
Section: Soil Remediation Technologymentioning
confidence: 99%
“…Several technologies such as modified electrokinetic remediation, bioremediation, in-situ chemical oxidation (ISCO), as shown in Table 1 , achieve high performance in less than a month 76 , 98 , 105 . Table 1 shows study periods at which different technological performances were reported.…”
Section: Cost Effectiveness Analysismentioning
confidence: 99%
See 1 more Smart Citation